2022
DOI: 10.1093/jrr/rrac042
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal sensation during total body irradiation: a prospective observational study

Abstract: Light flash and odor during radiotherapy are well-known phenomena. Two prospective observational studies have indicated that 55% of patients observed a light flash during irradiation of the retina and 27% of patients sensed an odor during radiotherapy for the nasal cavity. A prospective observational study was performed in all patients at our hospital who received total body irradiation (TBI) between January 2019 to October 2021. Light flash and odor during TBI were examined using the same method as that used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Ozone is an unstable substance and disappears in a short time, so the odor sensing rate may increase when the nasal cavity was included in the irradiated field. Our recent research showed the patients who received total body irradiation (TBI) felt odor (14 of 32 patients) and 2 of 14 patients answered “ozone” as the type of smell without knowledge of ozone as a possible cause ( 26 ). These reports indicate that ozone may be cause of the odor, however various types of odors have been reported in these reports as well ( 26 , 27 ), and it is not possible to identify the cause of the odors as ozone alone.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone is an unstable substance and disappears in a short time, so the odor sensing rate may increase when the nasal cavity was included in the irradiated field. Our recent research showed the patients who received total body irradiation (TBI) felt odor (14 of 32 patients) and 2 of 14 patients answered “ozone” as the type of smell without knowledge of ozone as a possible cause ( 26 ). These reports indicate that ozone may be cause of the odor, however various types of odors have been reported in these reports as well ( 26 , 27 ), and it is not possible to identify the cause of the odors as ozone alone.…”
Section: Discussionmentioning
confidence: 99%
“…A light flash is thought to be due to Cherenkov radiation and previous studies have suggested that this is triggered by irradiation of the retina [ 6 - 8 ]. The current study suggested that the chiasmatic gland is a significant factor for light sensation and that retina irradiation tends to be related to light sensation, although the results did not suggest significance.…”
Section: Discussionmentioning
confidence: 99%
“…Patients sometimes report abnormal visual (i.e., phosphene) and olfactory (i.e., phantosmia) sensations during radiation therapy (RT) [ 1 , 2 ]. While phantosmia indicates a phenomenon that an odor is perceived in the absence of an odorous stimulus [ 3 ], phosphene describes the phenomenon of visual sensations without light actually entering the eye [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…While phantosmia indicates a phenomenon that an odor is perceived in the absence of an odorous stimulus [ 3 ], phosphene describes the phenomenon of visual sensations without light actually entering the eye [ 4 ]. It is estimated that approximately 5–68% of the patients report a phosphene [ 2 , 5 ], and 4–44% of the patients report a phantosmia during RT [ 1 , 5 ]. However, phantosmia and phosphene are rare among the general population and uncommon among the clinical population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation